P-303 Cyclosporine Inhibits Down-regulation of Monocarbonic Acid Transporter 1 in Dextran Sodium Sulfate Induce Colitis. (February 2017) - Ota, Shinji; Sakuraba, Hirotake; Hiraga, Hiroto; Yoshida, Shukuko; Satake, Miwa; Hasui, Keisuke; Tanaka, Nahoko; Watanabe, Rina; Akemoto, Yui; Ishiguro, Yoh; Fukuda, Shinsaku
Abstract : Background: Cyclosporine showed a rapid improvement in the treatment of ulcerative colitis (UC). However the precise mechanisms remain unclear. Butyrate is short chain fatty acid, fermentation of gut microbiota, which is taken up into the intestinal epithelial cells (IECs) and acts as anti-inflammatory agent. Butyrate is transported into IECs by monocarbonic acid transporter 1 (MCT-1). Several reports described that MCT-1 expression was decreased in the colons of inflammatory bowel disease (IBD) patients. The aim of this study was to investigate the effects of cyclosporine on the regulation of MCT-1 of IECs in an experimental colitis model and Caco2 cells. Methods: Colitis was induced by feeding of 4% dextran sodium sulfate (DSS) in C57BL/6 mice and treated with vehicle- or cyclosporine by intraperitoneal administration. The body weight changes, histological damage scores and epithelial apoptosis scores were assessed. Expression of MCT-1 mRNA was assessed by real time PCR, and protein expression of MCT-1 was assessed by western blotting in purified IECs from DSS-treated mice. Butyrate concentrations of fecal contents were measured by high performance liquid chromatography mass spectrometry. Caco2 cells were incubated with or without cyclosporine and with or without Tumor Necrosis Factor (TNF)-α for 24 hours, and MCT-1 mRNA expression and protein expression were assessed. Results: Treatment of cyclosporine inhibited the body weight loss and mucosal damage through the reduction of epithelial apoptosis in DSS-treated mice. The downregulation of MCT-1 mRNA and protein expression in purified IECs from cyclosporine-treated mice at day 2 after DSS feeding was significantly inhibited compared with that in vehicle-treated mice. Fecal butyrate concentration was no difference between vehicle- and cyclosporine-treated mice. In Caco2 cells, the expression of MCT-1 was decreased in the presence of TNF-α. Treatment with cyclosporine alone did not influence the expression of MCT-1 by concentration- and time-dependent manner. However, cyclosporine ameliorated the impairment of MCT-1 expression by TNF-α. Conclusions: Cyclosporine ameliorated DSS-induced colitis, and inhibited the downregulation of MCT-1 in IECs. From these findings, the protective effect of cyclosporine is associated with butyrate transport through the regulation of MCT-1 expression.